Conformity in the Comfort of Anonymity: A Study on Derogatory Behavior in Social Media - Aini, Kurrota (Procedia of Social Sciences and Humanities, 2024)
This research aims to explore how anonymity impacts derogatory behavior among social media users. Through a qualitative method, this study analyzes the behavior of individuals during face-to-face interactions compared to when they use anonymous accounts o social media. The findings indicate that while participants generally behave politely in face-to-face interactions, they frequently adopt and reinforce negative group behaviors on social media when using anonymous accounts. This demonstrates that anonymity strengthens group conformity, leading to negative behavior on social media. This research reveals that anonymity often serves as a shield, enabling individuals to dissociate their online actions from their real-world identities and consequences, thus exacerbating irresponsible behaviors. The study suggests the importance of netiquette and the development of strategies to reduce online anonymity, which are crucial for fostering more responsible interactions on social media.